Target HeaTarget heading estimation using Lagrange difference method through bearing only measurementding estimation using Lagrange Difference formula through Bearing only measurement - Sindhu, B; Valarmathi, J; Christopher, S (International Journal of Engineering and Technology, 2018)
The bearing measurement in addition to the heading measurements increases the accuracy of the state estimate in bearing only tracking (BOT). Earlier, in [1] heading measurements are derived using set of three bearing measurements, mathematically known as centered difference method. In this paper we present the new approach using Lagrange three point difference method for deriving the heading measurements from set of bearing measurements. The performance analyses of the proposed approach is compared with the existing centered difference method using Root mean square error (RMSE), Root sum square error (RSSE) and maximum absolute error (MAE). The simulation results indicate that the Lagrange three point difference method performs comparatively better.